IMPLEMENTASI FATWA DSN MUI No:115/DSN-MUI/IX/2017 TERHADAP AKAD MUDHARABAH PADA TABUNGAN RENCANA IB DI BANK MEGA SYARIAH CABANG PALU - Bahraeni Lajamani; Ahmad Syafii; Suhri Hanafi (Tadayun: Jurnal Hukum Ekonomi Syariah, 2020)
This study is titled "Implementation of Fatwa DSN MUI No:115/DSN-MUI/IX/2017 against Mudharabah Agreement on Savings Plan at Bank Mega Syariah Palu Branch." The main issues are how mudharabah contract mechanism on iB plan savings at Bank Mega Syariah Palu Branch and how to Implement Fatwa No:115/DSN-MUI/IX/2017 against Mudharabah contract on Savings Plan at Bank Mega Syariah Palu Branch. The purpose of this research is to find out the Mechanism of Mudharabah agreement on iB savings plan at Bank Mega Syariah Palu Branch and how to Implement Fatwa DSN MUI No:115/DSN-MUI/IX/2017 against Mudharabah agreement on Savings Plan at Bank Mega Syariah Palu Branch.The research method used is a descriptive qualitative method. The results showed that the mechanism of Akad mudharabah at Bank Mega Syariah is not entirely in accordance with the provisions of the fatwa DSN MUI this desebabes the problem among human resources and the difficulties faced in the field. Bank Mega Syariah requires qualified administrators and employees not only related to their cognitive abilities but also related to the competence of moral attitudes.